(untitled) (Fiep Bulletin - online, 2011)
To be woman was perceived gradually, by the own development. The distinction among what was to be woman and what was to be men was explained by the cohabit with family in terms of what was allowed or denied to women. Thus, the motherhood is an important happening to every woman’s life. It’s when several responsabilities made by the woman (Woman, Mother, Nursing Student) conflict, sometimes prevailing one or other, forcing her to "reconcile" them. So, this study had as a goal to apprehend the meaning of being Woman, Mother and Nursing Student for nursing students from a privaty institution of higher education in a city in North of Paraná. It was a study of descriptive type, with qualitative approach, specifically a case study. The collect of data were accomplished in a period from september, 15 to september, 20, 2003. The tool used was formed by 3 guiding questions. Survey participants signed the Free and Informed Statement of Consent (FISC) and the research was submitted to Ethics in Research Committee (ERC) of that institution. It was made the interpretative analysis of data and were indentified the following categories to the meaning of to be Woman, Mother and Students: feelings, emotions and responsabilities. The interviewed age group ranged from 21 years old to 46 years old, most of them have 3 children, are married and leave their children with relatives.